Page 440
Contemporary Tribal Leaders of the Three Affiliated Tribes Following the passage of the Indian Reorganization Act of the 1934, the Mandan, Hidatsa and Ankara adopted a constitution on May 15, ] 936. Under the Indian Reorganization Act (IRA), the Tribes adopted a form of the American political governance structure. This form of government, however, was not new to the Three Affiliated Tribes. While the new constitution provided for a tribal council to replace the old business committee, the tribes had been operating under a representative form of government established in 1910. Prior to 1910, each village had individual leaders whether born into a leadership position or not. Voting was by consensus originating from each village. With the governance structure established in 1910, individuals were selected to represent each tribe and not village. The old business committee had consisted of equal representation from each tribe, two members each from Shell Creek and Nishu (formerly called Armstrong) and one each from Santee (Lucky Mound), Ree (Beaver Creek), Independence, Elbowoods, Little Missouri, and Red Butte. The new council was essentially the same. However, prominence was afforded leaders on the business council who carried out the operations of the Three Tribes. The following list is a compilation of the leaders of the tribal business council beginning with the Three Tribes adoption of the Indian Reorganization Act constitution in 1934. Many leaders of the tribe exist, who are not recognized as public officials (e.g. society members, medicine people, sacred bundle carriers, skilled artisans, and tellers of sacred stories) and have not been listed. However, it is important to understand that these individuals remain highly valued leaders and protectors of the tribe. These individuals, in some cases, direct the actions of tribal business leaders. Arthur Mandan - Mandan/Hidatsa 1936-1938 Arthur Mandan, Woman Spirit, was born in 1882 to Calf Woman and Howard Mandan Sr., Scarred Face, who was one of the first Mandan to go to an Indian boarding school in Santee, Nebraska. As a young man, he attended school at Carlisle Indian School in Pennsylvania where he was a member of the school band and an accomplished musician, a skill he continued throughout his adult life. He returned to Fort Berthold Reservation in 1908. As hereditary chief of the Mandan, he was the first triba chairman of the Three Affiliated Tribes to serve (September 1936 to August 1938), after the Three Tribes accepted the Indian Reorganization Act. He represented the district of Independence. A civic-minded man, Arthur Mandan was a liaison and interpreter for early eth- 440 2003-2005 North Dakota Blue Book